AL-SUNAN AL-MA’TSURAH: LIL IMAM MUHAMMAD BIN IDRIS AL-SYAFI’I
Hadith, as one of the Islamic scientific disciplines, does not miss out on contributing scientific wealth with the birth of works by scholars. The collection of hadiths in books by mukharrij hadiths is a very significant achievement in the Islamic world, both in what is then called primary books -kutubuttis'ah- and secondary ones.One of the heritage works in the field of hadith is the book Al-Sunan al-Ma's>rah lil Ima>m Muh